Squamomelanocytic Tumor, An Entity Still Shrouded in Mystery: Case Report and Literature Review - Joana Sorino; Mario Della Mura; Anna Colagrande; Cecilia Salzillo; Giuseppe Ingravallo; Gerardo Cazzato (Dermatopathology)
Cutaneous squamomelanocytic tumor (SMT) is a very rare cutaneous malignancy, composed of a dual phenotypic population of both malignant melanocytes and keratinocytes, intimately intermingled together. Herein, we report a new case of a SMT occurring in an 82-year-old man, located on the scalp. Histopathology revealed a mixed population consisting of squamous cell carcinoma and melanoma within the same lesion, also confirmed using immunohistochemical staining for high molecular-weight cytokeratins (HMWCKs) and Melan-A. Moreover, to the best of our knowledge, for the first time, we tested SMT for the preferentially expressed antigen in melanoma (PRAME), which revealed a strong and diffuse positivity in the melanocytic component. These tumors need to be distinguished by more frequent collision tumors and colonization. Furthermore, we provide a comprehensive review of the literature, focusing on clinical and histopathological aspects, biological behavior and still-debated, but fascinating histogenesis of this elusive entity.